Revitalizing the civilizational parameters in Said Nursi’s Weltanschauung : an ontological struggle - Kayadibi, Saim (2012)
The whole life span of Said Nursi is a summary of his ontological straggle which reflects the awareness of the reality of being created as a vicegerent (khalifatullah) of Allah on earth that is a great responsibility which was endowed by the Eternal Lord.It burdens on his shoulder to implement these awareness. This responsibility maintained since the creation of the first man. In order to be aware of this reality, the fundamental parameters must be kept vibrant and these parameters are mainly the ontological consciousness, science and knowledge (epistemology), value (axiology), ummatic/humanity responsibility, the civilizational memory, the sense of self perception, self-confidence, and social cosmology. These values automatically accelerate the psychological motivation of Muslim individuals and masses to stand back against secularistic, materialistic, injustice, monopolistic as well as hegomonistic mentality. Once Said Nursi realized his great responsibility as the vicegerent (khalifatullah) of Allah on earth, it persuaded him to reawaken his ontological consciousness to be a significant being rather that an artificial element or subject on earth. With a strong faith and being an action man creates unbelievable revolutions. Along with the rest of the Ottoman Empire as the heart of the Caliphate of Islam, atheism, secularism and materialism became fashionable in the Western world as well as in Turkey. All the senses for the religious valueshave been declared enemy, and consequently dreadful cruelties made towards believers in order to destruct all the religious values. These attacks made on the foundations of the faith by the secularists and materialists in the name of science, nature and politics. As one of the many Sufi leaders and faith survivors, Said Nursi (ks) responded to these secularistic and materialistic attacks especially in Turkey via devoting all his life to protect and reinforce the most important maqasid al-shari‘ (the high objective of the Lawgiver) for human beings. This paper, therefore, investigates the ontological struggle of Said Nursiagainst the secularistic and materialistic approaches to revitalize the inner dimensions of the Islamic Civilization from his Weltanschauungtaking into consideration of the latest movie made on him as Free Man “Hür Adam”.